Catalytic oxidative hydrothermal treatment of palm oil mill effluent over CuO/Al2O3 and Ce-CuO/Al2O3 catalysts - Lee, Zhan Sheng (2022)
This study aspires to investigate the performance of novel non-oxidative and oxidative subcritical hydrothermal treatments (NOHT and OHT, respectively), followed by catalytic oxidative hydrothermal treatment (COHT) of palm oil mill effluent (POME). Hydrothermal reaction is commonly used in wet biomass treatment, but it had never been used in POME treatment before this research was conducted. The high reaction temperature and time of hydrothermal process and catalyst activity in an aqueous environment are problems to be addressed. Hence, the objectives of this research are to investigate the performance of hydrothermal reactions and catalytic reactions as well as to propose the reaction mechanisms. The experiments of OHT and NOHT were conducted using 500 mL POME of initial COD and BOD5 at 52200 mg/L and 18020 mg/L, respectively, at different temperatures (493-533 K) and reaction times (2-8 h). Meanwhile, the experiments of COHT were performed using a similar working volume of POME over two types of catalysts, i.e., CuO/Al2O3 and Ce-CuO/Al2O3, at loadings of 0.2, 1.0, and 2.0 mg/ml at 533 K for 8 h. The dominant component of fresh POME, i.e., n-hexadecanoic acid, gradually reduced in the liquid products of NOHT and OHT in reactions with elevated temperatures. Carboxyl compounds reduced while phenolic components increased as reaction temperature increased over NOHT. The gaseous products of NOHT contained carbon dioxide (CO2), carbon monoxide (CO), hydrogen gas (H2), and C3-C6 hydrocarbons. Traces of methane gas (CH4) were only found at 533 K due to subcritical hydrothermal gasification at low temperatures. The decolourisations of POME in NOHT and OHT were 7.02% and 54.10% respectively at 533 K and 8 h, indicating the notable performance of OHT in decolourising POME. At 533 K and 8 h, NOHT achieved the highest reductions of chemical oxygen demand (COD) and five-day biochemical oxygen demand (BOD5) at 61.4% and 68.0%. However, the OHT reaction resulted in better removals of COD and BOD5, recording 81% and 87% respectively, with the pH of the liquid product approaching 6.5 from the initial value of 3.5 at the same reaction temperature and time. Notwithstanding, COHT of POME achieved more remarkable performance than the non-catalytic reactions. At a loading of 2.0 mg/ml catalyst in COHT, Ce-CuO/Al2O3 recorded 86.1% COD and 94.7% BOD5 removals at 533 K and 8 h, where its performance was slightly better than CuO/Al2O3 (79.4% COD and 93.8% BOD5 removals). The increase of catalysts loading after 1.0 mg/ml did not contribute any significant difference in degrading the pollutants of POME, suggesting the adequacy of using 1.0 mg/ml catalysts viewing from the technical and economic aspects. The reusability test of spent Ce-CuO/Al2O3 catalysts showed insignificant leaching of Cu and Al elements, and the reductions of COD and BOD5 were as high as 75.4% and 85.2% respectively, indicating no significant deactivation of catalysts up to three reaction cycles. In the derivation of kinetic rate law, a second-order kinetic conformed well to experimental data of COHT with correlation coefficients greater than 0.90 and an error of less than 5% between the estimated and experimental findings. For the mechanism studies, POME in NOHT decomposed into water-soluble compounds, followed by deoxygenation (dehydration and decarboxylation) in producing hydrochar with lower oxygen content and higher aromatic compounds in the liquid product. On the other hand, the reaction mechanism was dominated by the free radicals’ reaction in COHT. The experimental findings have successfully revealed the potential of this novel POME treatment method in substituting the conventional treatment process. This novel study could act as a foundation for the scalability and commercialisation of hydrothermal processes in POME treatment in the future.